Standard Patterns of Considerations in Law, District Regulation and Qanun Based on Legal Rules in Indonesia - Husna Sartika; Eddy Purnama; Ilyas Ismail (Fakultas Hukum Universitas Lampung, 2021)
The consequence of the state of the law is legislation to be an essential instrument in regulating public life. However, in some parts of Indonesia, they can make their regional regulation slightly different from the constitution, wherein this article will focus on Qanun in Aceh Province. The research used in this paper is normative law research. This research used sequential data or library data. Secondary data consists of primary law materials, secondary law materials, and tertiary law materials. The approach method used is the legislative approach and the conceptual approach. The formulation of the problem in this paper is how the standard pattern of consideration in the Law, Regional Regulations, and Qanun is based on legislation. The results show that in the Law in Consideration, Consider using the word